Elevated expression of ciRS-7 in peripheral blood mononuclear cells from rheumatoid arthritis patients - Xinyi Tang; Jiemin Wang; Xin Xia; Jie Tian; Ke Rui; Huaxi Xu; Shengjun Wang (BMC, 2019)
Abstract Background Circular RNAs (circRNAs) represent a class of widespread and variety endogenous RNAs that may regulate gene expression. Thousands of mammalian circRNAs harbor miRNA response elements (MREs), suggesting a potential role as competitive endogenous RNAs (ceRNAs). Recent studies have demonstrated that ciRS-7 (circular CDR1 antisense), which acts as a powerful miR-7 sponge, contains more than 70 putative binding sites for miR-7 and may inhibit its target genes. The aim of this preliminary study was to investigate the expression of ciRS-7 in patients with rheumatoid arthritis (RA) as well as the correlation between ciRS-7 and the target genes of miR-7. Methods Eighteen patients with RA and 14 healthy controls were enrolled in the current study. The relative expression of ciRS-7, miR-7, miR-671 and mTOR in peripheral blood mononuclear cells (PBMCs) from these samples were detected by real-time PCR. Results We found that ciRS-7 was significantly increased in RA patients and could potentially differentiate the RA patients from healthy controls. Additionally, the expression of mTOR, one of the miR-7 target genes, had positive and negative relationships with ciRS-7 and miR-7 expression, respectively. Notably, the relative expression of miR-671, which mediated the regulation of circular CDR1 antisense homeostasis, was significantly decreased in RA patients. Conlusion Downregulated miR-671 may influence the level of ciRS-7 in RA patients. Enhanced ciRS-7 could inhibit the function of miR-7 and further relieve the inhibitory effect of miR-7 on mTOR.